The Relationship Between Smoking Status and Smoking Index Against COVID-19 Disease Course in Treated Patients at Dr. M Djamil General Hospital, Padang - Yulia Helexandra; Yessy Susanty Sabri; Fenty Anggrainy (Respiratory Science, 2022)
Background: Smoking is a risk factor for the development and worsening of respiratory diseases, including COVID-19 infection. Smoking can increase the risk of the severity of COVID-19 by two times because in smokers there is an increase in the expression of the ACE-2 gene by 25% compared to non-smokers. The purpose of this study was to determine the relationship between smoking status and smoking index on the course of COVID-19 disease treated at Dr. M Djamil General Hospital. Method: An observational analytic study with a retrospective cohort approach on COVID-19 patients who were treated at Dr. M. Djamil General Hospital. Data were taken from January to March 2021. The relationship between smoking status and smoking index on the course of COVID-19 was analyzed by Chi-Square. Results: This study found the most age was above 50 years with a vulnerable age of 50-59 years (28.4%) and female gender (56.7%). Non-smoker status (64.2%) and moderate smoking index (51.4%) were the most commonly found in this study. Clinically non-progressive COVID-19 (53.7%) was the most common. This study found that the maximum length of stay for COVID-19 patients was less than 21 days (53.7%) and the outcome of patients recovered (62.2%). This study found a significant relationship between the smoking index on the clinical progress of COVID-19 patients and there was a significant relationship between smoking status and the outcome of COVID-19 patients. This study found that smoking status and the smoking index had no significant relationship with the length of stay of COVID-19 patients. Conclusion: Smoking status is related to outcomes in COVID-19 patients and the smoking index is related to a progression in COVID-19 patients treated at Dr. M. Djamil General Hospital.